2000
DOI: 10.1016/s0002-9440(10)65053-5
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and Tumor Necrosis Factor-α Determine Resistance to Paracoccidioides brasiliensis Infection in Mice

Abstract: To investigate the role of interferon-gamma (IFN-gamma) and tumor necrosis factor-alpha (TNF-alpha) in the resistance to Paracoccidioides brasiliensis (Pb) infection, mice with homologous disruption of the IFN-gamma (GKO) or TNF-alpha receptor p55 (p55KO) were infected with the parasite. GKO and p55KO, but not wild-type (WT) mice, were unable to control the growth of yeast cells and the mice succumbed to infection by days 16 and 90 after infection, respectively. Typical inflammatory granulomas were found only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
128
1
37

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(177 citation statements)
references
References 43 publications
11
128
1
37
Order By: Relevance
“…Although we presented no direct evidence in humans that GM-CSF treatment will protect transplant patients from bacterial infection under immunosuppression, we have shown in vivo both in an infection and an infection/transplantation mouse model that GM-CSF restores innate immunity against infections to strengthen this hypothesis. In addition, TNF is known to be crucial in the host defense against infections (15)(16)(17). Indeed, the neutralization of TNF bioactivity, as recently approved for the treatment of Crohn's disease or rheumatoid arthritis, was associated with the development of active tuberculosis in some patients (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we presented no direct evidence in humans that GM-CSF treatment will protect transplant patients from bacterial infection under immunosuppression, we have shown in vivo both in an infection and an infection/transplantation mouse model that GM-CSF restores innate immunity against infections to strengthen this hypothesis. In addition, TNF is known to be crucial in the host defense against infections (15)(16)(17). Indeed, the neutralization of TNF bioactivity, as recently approved for the treatment of Crohn's disease or rheumatoid arthritis, was associated with the development of active tuberculosis in some patients (38).…”
Section: Discussionmentioning
confidence: 99%
“…Such a status requires a preferential reactivation of the effectors of the innate immune responses, i.e., macrophages and/or neutrophils, by pharmacological intervention without restoring the suppressed adaptive immune responses, such as the T cell response, which is implicated in graft rejection (11)(12)(13). Recombinant GM-CSF, a drug approved for hematological indications in humans (14), has been indicated in vitro and in vivo to enhance the synthesis and release of proinflammatory cytokines such as TNF, which is crucial in host defense in various animal infection models (15)(16)(17). In our laboratory it was previously shown that GM-CSF potentiates the immune responses to endotoxin (18) and restores the impaired immune responses in LPS-desensitized mice (19) as well as in refractory human monocytes (20).…”
mentioning
confidence: 99%
“…Considering the central role of these cells in the initiation as well as the effector function of the immune response, the low efficiency in stimulating production of Th1 cytokines such as IFN-g could be implicated in the determination of a susceptible pattern in vivo. Several reports have shown that resistance to P. brasiliensis infection is linked to IFN-g production (43,44). Based on the present data, it is tempting to speculate that distinct antigen-processing mechanisms of APC in resistant and susceptible mice, such as the expression of genetic differences in the ability to take up antigens, qualitative and quantitative expression of MHC class II antigens and differences in the proteolytic machinery for antigen processing, may be involved in determining a susceptibility pattern to P. brasiliensis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The protective host immunity includes Th1-type response, in which IFN-␥ and TNF-␣ (3,5,6) are fundamentals to control of fungus dissemination and death. However, the patients with PCM usually show impaired cellular immune response to fungal Ags (3,7,8).…”
Section: O Ne Of the Most Important Endemic Diseases In Latinmentioning
confidence: 99%